2014
DOI: 10.1007/s10552-014-0408-0
|View full text |Cite
|
Sign up to set email alerts
|

Serum uric acid levels and cancer mortality risk among males in a large general population-based cohort study

Abstract: PurposeSerum uric acid (SUA) has antioxidant capacities and therefore may protect against the development of cancer. Few epidemiological studies have tested this hypothesis, and findings were inconsistent.MethodsWe studied the association between SUA levels and mortality due to any type of cancer, and three common types of cancer among males (lung, colorectal, and prostate cancer) in the general population-based Vlagtwedde–Vlaardingen cohort with 38 years of follow-up and 8 surveys (total number of males = 4,3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
34
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 27 publications
6
34
0
1
Order By: Relevance
“…Our results are in accordance with most large, prospective cohort studies although one cohort study conducted by Taghizadeh et al 15 demonstrated that higher levels of SUA were related to a lower risk of cancer mortality, supporting a protective role of SUA in the risk of cancer mortality. Kolonel et al 16 found elevated baseline SUA levels were not associated with the risk of overall cancer and most subtypes of cancer, but were only positively associated with the risk of developing prostate cancer in Japanese men [adjusted RR: 1.5, (95% CI: 1.1-2.1)].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results are in accordance with most large, prospective cohort studies although one cohort study conducted by Taghizadeh et al 15 demonstrated that higher levels of SUA were related to a lower risk of cancer mortality, supporting a protective role of SUA in the risk of cancer mortality. Kolonel et al 16 found elevated baseline SUA levels were not associated with the risk of overall cancer and most subtypes of cancer, but were only positively associated with the risk of developing prostate cancer in Japanese men [adjusted RR: 1.5, (95% CI: 1.1-2.1)].…”
Section: Discussionsupporting
confidence: 92%
“…Our results are in accordance with most large, prospective cohort studies although one cohort study conducted by Taghizadeh et al . demonstrated that higher levels of SUA were related to a lower risk of cancer mortality, supporting a protective role of SUA in the risk of cancer mortality.…”
Section: Discussionsupporting
confidence: 92%
“…Conclusions similar to those above reported were suggested by the positive clinical outcome, which was associated with elevated uric acid serum levels . The protection against cancer mortality given by elevated serum uric acid levels was demonstrated by a large general population‐based cohort study with 4350 patients who died because of cancer, in particular, cancer localized to the lung, colorectal intestine, and prostate .…”
Section: Role Of Xanthine Oxidoreductase In Differentiation and Oncogsupporting
confidence: 73%
“…Growing evidence suggests that hyperuricemia is associated with cancer mortality, 10,14 although the observational data are inconsistent. 13 Hyperuricemia, resulting from high nucleic acid turnover in the rapidly proliferating tumor burden 35 or indicating tumor lysis syndrome, 36 is often observed in individuals with cancer. A significantly positive correlation was previously reported between hyperuricemia and death from cancer.…”
Section: Discussionmentioning
confidence: 99%